A guide to financing mechanisms in international business transactions - Kim, Sang-man (Cambridge Scholars Publisher, 2019)
This book outlines features of international business transactions, and discusses their various associated risks. For the successful completion of an international business transaction, depending on its terms, both parties need access to funds. This text deals with financing mechanisms mainly in the international sale of goods and in overseas construction projects. Concerning financing international sale of goods, it discusses export working capital financing, documentary credit, negotiation of bills of exchange, export factoring, and international forfaiting. Concerning financing an overseas.